2019
DOI: 10.3390/ijerph16245020
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Weeks of Combined Resistance and Aerobic Exercise Improves Cardiometabolic Biomarkers and Enhances Red Blood Cell Hemorheological Function in Obese Older Men: A Randomized Controlled Trial

Abstract: The present study examined the effect of a 12-week combined resistance and aerobic exercise training program on cardiometabolic biomarkers and red blood cell (RBC) hemorheological function in 20 obese older men (mean age: 68.8 ± 0.9 years). Subjects were randomly divided into two groups (exercise intervention [EXP; n = 10] and control [CON; n = 10]). The EXP subjects performed resistance and aerobic exercise training program three times per week for 12 weeks, and the CON subjects maintained their regular lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…While the exercise intervention group in the present study showed the tendency of increased fat-free mass after 12 weeks, the control group exhibited a considerable decrease in fat-free mass over the time point. This result was similar to previous studies in which resistance exercise alone and combined aerobic- and resistance-exercise significantly increased the fat mass more than aerobic exercise alone in overweight or obese adults [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…While the exercise intervention group in the present study showed the tendency of increased fat-free mass after 12 weeks, the control group exhibited a considerable decrease in fat-free mass over the time point. This result was similar to previous studies in which resistance exercise alone and combined aerobic- and resistance-exercise significantly increased the fat mass more than aerobic exercise alone in overweight or obese adults [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Muscle activation during submaximal exercise with the same relative exercise intensity under hypoxic conditions was higher than that under normoxic conditions [49], and increased muscle activation under hypoxic conditions is likely to increase NO production in the endothelium, and improve vasodilation and endothelial functions [48,50]. Consequently, exercise under hypoxic conditions might elicit upregulation of NO synthase and induce an additive effect on the secretion of various vasodilators (e.g., adenosine, prostaglandin, and NO) and vascular endothelial growth factor, resulting in an additive effect on the improvement of endothelium-dependent vasodilation, reduction of arterial stiffness, and microcirculation through improved hemorheological functions [13,15,[22][23][24][25]44].…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent hypoxic exposure enhances endothelial-derived nitric oxide-mediated mechanisms that are primarily involved in the vasodilation of muscular arteries; as a result, it is frequently applied to lower the blood pressure of patients with hypertension [20,21]. In addition, exercise intervention under hypoxic conditions induces an additive effect on the secretion of various vasodilators (e.g., adenosine, prostaglandin, and nitric oxide [NO]) and vascular endothelial growth factor, which leads to an additive effect on the improvement of vasodilation, reduction of arterial stiffness, and microcirculation through improved hemorheological functions [13,15,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing these factors, which are related to endurance exercise performance, increases the efficiency of aerobic energy production and consequently enhances maximum oxygen uptake (VO 2 max). It also enhances athletic performance by improving time until fatigue and increasing exercise intensity [3][4][5][6]. In particular, endurance exercise performance is reported to be the most affected by hemodynamic function, which is an indicator of oxygen transport and utilization ability [7].…”
Section: Introductionmentioning
confidence: 99%